2017
DOI: 10.17221/472/2017-pse
|View full text |Cite
|
Sign up to set email alerts
|

Season, location and cultivar influence on bioactive compounds of sour cherry fruits

Abstract: The aim of this study was to determine how different locations, years and cultivars influenced polyphenol and anthocyanin content in fruits of different sour cherry cultivars (Prunus cerasus L.). Fruits of five sour cherry cultivars were harvested in two locations (Osijek and Zadar) over three consecutive years (2010, 2011 and 2012). Factorial ANOVA showed that year and location significantly influenced the accumulation of polyphenols and anthocyanins in sour cherry fruits. 2010 was the best year with 9.89 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 26 publications
0
5
1
1
Order By: Relevance
“…This is well in agreement with ours results. Viljevac Vuletić et al (2017) have indicated that higher level of precipitation at the site has a positive impact on the content of bioactive substances in the plant, which we unfortunately did not confirm in this study. The higher content of total polyphenols, sulphur compounds and antioxidant activity was recorded in the locality with increasing average annual temperature in Nitra.…”
Section: Bardejovcontrasting
confidence: 83%
See 1 more Smart Citation
“…This is well in agreement with ours results. Viljevac Vuletić et al (2017) have indicated that higher level of precipitation at the site has a positive impact on the content of bioactive substances in the plant, which we unfortunately did not confirm in this study. The higher content of total polyphenols, sulphur compounds and antioxidant activity was recorded in the locality with increasing average annual temperature in Nitra.…”
Section: Bardejovcontrasting
confidence: 83%
“…Polyphenols, especially flavonoids are synthesized via the phenylpropanoid pathway with stimulation of light, which protects plants from harmful UV radiation acting as a protective filter. High temperatures during the season contributed to higher polyphenols content (Viljevac Vuletić et al, 2017).…”
Section: Bardejovmentioning
confidence: 99%
“…The nutritional composition of the harvested fruit can be modulated by growing conditions [8]. In fact, Viljevac et al [41] concluded that geographical location had a strong impact on polyphenol and anthocyanin contents of various sour cherry cultivars. However, current globalization makes it possible to obtain fruits and vegetables from various regions all over the world and all year round.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from their different chemical compositions, properties and use, both crop types are members of the genus Prunus, from the stone fruit family Rosaceae [13]. In addition to other stone fruit types, sour cherries and apricots have been the subject of comprehensive research by many authors due to their rich chemical composition and desirable sensory properties [14][15][16][17][18][19]. A close link between the present bioactive compounds and their positive impact on human health has been established [20,21].…”
Section: Introductionmentioning
confidence: 99%